A Review on Emerging Contaminants in Indian Waters and Their Treatment Technologies - Mathew, Riya Ann; Kanmani, S. (Nature environment and pollution technology, 2020)
Emerging contaminants (ECs) have been detected recently in many water bodies across India. Studies have found the presence of ECs in surface water, groundwater, stormwater, treated wastewater, treated industrial effluent, bottled water and snow from glaciers in Indo-Chinese border which contaminate water bodies. The surface water recharges the groundwater, thereby the ECs make their way to deep water aquifers. The soil also gets contaminated and plants can uptake ECs. These micropollutants can cause adverse ecological and human health effects. Antimicrobial resistance of bacteria to commonly used antibiotics has been observed in India. An exhaustive review of emerging contaminants in Indian waters and their treatment technologies has been carried out. Antibiotic-resistant genes can be easily transferred resulting in a plethora of antimicrobial-resistant bacteria which can cause devastating effects on human health. Conventional biological treatment is not capable of removing ECs completely. Advanced oxidation processes using ozonation and visible light active photocatalyst are a sustainable solution for the removal of most ECs. Hence, it is of utmost importance to monitor the presence of ECs in the water environment and develop treatment technologies for its removal.